A Novel Soft Bending Actuator Using Combined Positive and Negative Pressures - Fatahillah, Mohammad; Oh, Namsoo; Rodrigue, Hugo (Frontiers in Bioengineering and Biotechnology, 2020)
Most soft pneumatic actuators for producing bending actuation have made use of either positive or negative pressure and adjusted their design in consequence. In the proposed paper, a novel soft bending actuator using combined positive and negative (PNP) pressures for actuation is presented that is capable of producing a blocked force as high as 150 N while still being able to produce large bending deformations. In this actuator, the bending force of a negative pressure actuator and a positive pressure actuator is combined in a single actuating structure. It was found that the equilibrium angle of PNP actuation is lower than using only negative pressure but that the actuator can produce larger forces at angles below the equilibrium angle of using positive pressure only. The actuator can use PNP actuation to produce large forces at lower bending angles and negative pressure actuation for producing large bending angles. This actuator was implemented in a soft robotic gripper capable of lifting large objects weighing up to 4 kg and a soft pinching gripper capable of holding a notebook weighing 1.85 kg by pinching it. The proposed actuator is capable of large forces and is versatile such that it is expected to be used in applications such as agriculture where many objects tend to be large and heavy yet require a delicate touch.